ANALYSIS OF CONSTRAINTS TO EFFECTIVE AGRICULTURAL EXTENSION SERVICE DELIVERY AND ITS IMPACT ON AGRICULTURAL PRODUCTIVITY IN OHIMINI LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Omale, P.I.; Agabidu, P.E.; Ajeh, O.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed the constraints to agricultural extension service delivery and its impact on agricultural productivity in Ohimini Local Government Area of Benue State, Nigeria. Data were collected from 120 respondents selected through a multistage random sampling technique using a structured questionnaire. Descriptive statistics such as frequencies, percentages, means, and standard deviations were employed for data analysis, while multiple regression and simple linear regression were used to test the hypothesis. The results showed that majority (60%) of the respondents were male, with an average age of 44 years and mean farming experience of 16 years. The most (80%) of the respondents were full-time farmers. The major constraints affecting extension services included insufficient operational funds (Mean = 3.55), poor road networks (Mean = 3.53), inadequate number of agents (Mean = 3.48), and irregular visitation (Mean = 3.42). These challenges significantly reduced extension efficiency and farmers’ participation in innovation programs. Regression analysis revealed that sex, education, income, farm size, farming experience, membership in farmers’ organizations, and proximity to extension service points significantly influenced access to extension services (R² = 0.482, p < 0.05). Furthermore, the hypothesis test indicated a negative and significant relationship (β = -0.456, p < 0.001) between extension constraints and agricultural productivity, implying that productivity declines as constraints increase. The study concludes that underfunding, poor infrastructure, and limited manpower are key limitations of the extension system. It recommends increased funding, recruitment and training of personnel, integration of ICTs, participatory approaches, and gender-sensitive programming to improve the efficiency and impact of agricultural extension delivery in Benue State.